Innovative technology for dough shells in minced semi-finished products based on the synergy of gluten-free raw materials and microalgae protein isolate for military and healthy diet - Helikh, Anna; Yongfeng, Pang; Геліх, Анна; Юнфень, Пан (Запоріжжя : Видавничий дім «Гельветика», 2026)
EN: This research presents a comprehensive theoretical and experimental framework for advancing the technology of dough shells used in dual-use minced semi-finished products, specifically tailored for military rations and crisis-resiliant nutrition. We have scientifically validated the integration of a protein isolate derived from the microalga Euglena gracilis alongside a selection of gluten-free plant materials, including rice, white lupin, flaxseed flour, and corn starch. This strategic formulation is designed to enhance both the nutrient density and biological value of the final product. Furthermore, it addresses a critical gap in specialized nutrition by catering to individuals suffering from gluten intolerance or stress-induced exacerbations of celiac disease. In evaluating the functional, technological, and rheological performance of these model dough systems, our findings highlight a significant synergy between white lupin flour and the microalgae isolate. This interaction provides the structural and mechanical resilience necessary to maintain the integrity of the dough shells under the rigors of extreme logistics, deep freezing, and field-based thermal processing. By identifying the optimal balance between protein fortifiers and structure-forming agents, we have established a robust production technology for high-energy, special-purpose dough shells. Comprehensive assessments of organoleptic, physicochemical, and safety parameters further confirm that this technology offers an effective solution for ensuring sustainable nutrition and food security in demanding environments. /// UA: Виконані комплексні дослідження, що дозволяють теоретично та експериментально обґрунтувати удосконалення технології тістових оболонок для фаршевих напівфабрикатів подвійного призначення – для раціонів військового харчування та використання у кризових ситуаціях. Науково обґрунтовано доцільність введення ізоляту білка мікроводорості Евглени (Euglena gracilis) у комплексі з безглютеновою рослинною сировиною (рисовим, білого люпину, льняним борошном та кукурудзяним крохмалем) як фізіологічно-функціональних інгредієнтів. Таке композиційне рішення спрямоване на підвищення нутрієнтної щільності та біологічної цінності продукту, а також задоволення потреб споживачів зі стрес-індукованими загостреннями целіакії та непереносимістю глютену. Досліджено функціонально-технологічні та реологічні властивості модельних тістових систем. Встановлено, що синергія борошна білого люпину та ізоляту мікроводоростей забезпечує необхідну структурно-механічну міцність тістових оболонок, що гарантує збереження їх цілісності під час екстремальної логістики, заморожування та термічної обробки в польових умовах. Визначено оптимальне співвідношення білкових збагачувачів та структуроутворюючих компонентів у рецептурі. Розроблено комплексну технологію виробництва високоенергетичних тістових оболонок для фаршевих напівфабрикатів спеціального призначення. Досліджено органолептичні та фізико-хімічні показники, а також основні показники безпеки тістових оболонок, що підтверджують його ефективність для забезпечення продовольчої безпеки та сталого харчування.
Інноваційна технологія тістових оболонок для фаршевих напівфабрикатів на основі поєднання безглютенової сировини та ізоляту білка мікроводоростей для військових раціонів та харчування у кризових ситуаціях
Keywords: alternative proteins; microalgae protein isolate; Euglena gracilis; flour-based dough shells; military nutrition; crisis-resiliant nutrition; gluten-free diet; white lupin flour; альтернативні білки; ізолят білка мікроводоростей; борошняні тістові оболонки; військове харчування; кризостійке харчування; безглютенова дієта; борошно люпину білого